2008
DOI: 10.1007/s00128-008-9501-y
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Toxic Substances in Agricultural Soils of Lishui County, Jiangsu Province, China

Abstract: The contamination status and distribution of PTS, including HCHs, DDTs, PCBs, and PAHs, were studied in the agricultural soil of Lishui County, one of China's nationally designated eco-demonstration region. The PTS was analyzed by GC, GC/MS, and HPLC coupled with microwave extraction. The concentrations of the sum of HCHs, DDTs, and PCBs ranged from <0.1 ng g(-1) to 133 ng g(-1), 93.8 ng g(-1), and 81.0 ng g(-1) (dry wieght), respectively; while the contents of the sum of PAHs ranged from 3.26 ng g(-1) to 91.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Thus, the heavier homologues generally tend to be retained by the soil more than the lighter ones. The results in nearby regions that showed that the pentachlorinated and hexachlorinated PCBs were the dominant congeners in leaves and agricultural soil were consistent to the congener profiles in Taicang vegetable soil [3,11,13,14]. But the paddy field is often covered by water and less cultivated than the vegetable fields, which decreases the chance of PCBs atmosphere-soil exchange especially the lighter homologues with higher vapor pressure and increases the dechlorination of heavier chlorinated congeners.…”
Section: Pcb Congeners Profiles Under Different Lutssupporting
confidence: 80%
See 2 more Smart Citations
“…Thus, the heavier homologues generally tend to be retained by the soil more than the lighter ones. The results in nearby regions that showed that the pentachlorinated and hexachlorinated PCBs were the dominant congeners in leaves and agricultural soil were consistent to the congener profiles in Taicang vegetable soil [3,11,13,14]. But the paddy field is often covered by water and less cultivated than the vegetable fields, which decreases the chance of PCBs atmosphere-soil exchange especially the lighter homologues with higher vapor pressure and increases the dechlorination of heavier chlorinated congeners.…”
Section: Pcb Congeners Profiles Under Different Lutssupporting
confidence: 80%
“…Backe et al reported that PCB concentrations in soils of south Sweden showed a large variation between various sampling sites, and PCB congener composition was shown to differ between sites, with congener patterns almost site-specific [19]. The studies in nearby region Zhangjiangang, Changsu, and Lisui showed that PCB 118 had the highest concentration in all congeners of PCBs in soil [3,14]. But the study in Tai Lake, Hangzhou Bay and Shanghai City region showed the PCB 138 was the highest concentration congener in agricultural soil [13].…”
Section: Pcb Congeners Profiles Under Different Lutsmentioning
confidence: 93%
See 1 more Smart Citation
“…The mean concentrations of soil total PAHs in all districts were greater than 3000 lg/kg. Maliszewska-Kordybach (1996) developed a classification system of contamination of soils by PAHs (Table 2) based on studies of PAH concentrations in European soils, as well as from an estimation of risk of human exposure, and the classification has been widely accepted and cited (Morillo et al 2008;Hu et al 2009). According to the classification system all the sampling areas apart from an urban park can be considered to be heavily contaminated with PAHs.…”
Section: Pah Concentrations and Distribution In Areas Of Differing Lamentioning
confidence: 99%
“…Ultrasound-assisted solvent extraction (UASE) (Errekatxo et al 2008;Rocco et al 2008), microwave-assisted extraction (MAE; Hu et al 2009), supercritical fluid extraction (SFE; Song et al 2002), and pressurized liquid extraction (PLE; Antunes et al 2009) have recently been used to circumvent the shortcomings of classical extraction methods for this purpose.…”
Section: Analytical Pretreatment Of Samplesmentioning
confidence: 99%